Electromagnetic model of a nanodipole array above a double‐layer graphene by periodic green's function. Issue 15 (30th October 2020) - Cruz, André; Costa, Karlo; Dmitriev, Victor; Souza, Nadson; Zaman, Quaid; Del Rosso, Tommaso
Abstract : In this study, the authors present an electromagnetic model of a nanodipole array above a double‐layer Graphene (DLG) operating at Terahertz. The graphene layers deposited between the dielectric mediums are modelled as surface impedances with conductivities described by the Kubo model. The electromagnetic fields are defined by the spectral representation of the periodic Green's function with impedance condition between the mediums. The main objective of this work is to propose an equivalent and analytical electromagnetic model of a nanodipole array above a DLG, which can be used to describe a surface plasmon resonance sensor that operates at the terahertz frequency. As a way of validating the method, the authors compared the proposed model with a software based on the finite element method. In addition, still, as a form of validation, the authors verified the convergence of the method from the spectral analysis of the proposed Green's Function. As results, spatial and spectral parametric analyses are shown as a function of the concentration of nanodipoles in the array, and the chemical potential applied to the graphene layers. In these results, the authors verify the appearance of plasmonic, optical and acoustic modes, and their contributions in the total field.